Type 2 diabetes, cardiovascular risk factors and offspring overweight and obesity 5 to 6 years after hyperglycaemia first detected in pregnancy in Cape Town, South Africa - Chivese, Tawanda (Department of Medicine, 2021)
Background The number of people with type 2 diabetes mellitus (T2DM) is increasing rapidly in Africa, straining already overstretched health systems. The association between hyperglycaemia first detected in pregnancy (HFDP), which includes both diabetes mellitus in pregnancy (DIP) and gestational diabetes mellitus (GDM), and the later development of T2DM and cardiovascular disease risk in the mothers and possibly overweight in their children is well recognised. This thesis contributes to the largely unexplored body of work on the prevalence of T2DM and CVD risk factors in African women after HFDP and the relationship between HFDP and childhood overweight and obesity. The thesis investigated: 1) the prevalence of T2DM and impaired glucose metabolism in African women of childbearing age; 2) the prevalence of T2DM and cardiovascular disease risk factors in women within 6 years after HFDP, and 3) the influence of maternal blood glucose levels during pregnancy and overweight and obesity in the offspring at the preschool age. Methods A systematic review and meta-analysis of all studies published from January 2000 to 2017 was carried out to estimate the prevalence of T2DM and impaired glucose regulation states. In the PROgression to Diabetes study (PRO2D), women diagnosed with GDM using the 2008 National Institute for Health and Care Excellence (NICE) criteria during 2010 and 2011 at a major referral hospital and their offspring were reviewed up to 6 years later. Relevant maternal and foetal/neonatal data were routinely collected during pregnancy and birth. The women were recalled for an assessment of T2DM (OGTT and HbA1C) and other cardiovascular risk factors (insulin resistance, dysglycaemia, dyslipidaemia and obesity) and their offspring for overweight/obesity. The women were reclassified into DIP and GDM using the WHO 2013 criteria for the diagnosis of HFDP. The pooled prevalence of T2DM was; 7.2% (95% CI 5.6% to 8.9%), impaired fasting glycaemia, 6.0% (95% CI 4.2% to 8.2%) IGT, 0.9% to 37.0% from 39 studies in 27 African countries, and 53 075 participants. The response rate for the PRO2D was 44.2% (final sample n=220). At follow up, almost half of the women, [48% (95% CI 41.2–54.4)], had T2DM, 83% in the DIP subtype and 31% with GDM had T2DM. The type of treatment [insulin (OR 25.8, 95% CI 3.9–171.4, p = 0.001), oral antidiabetic drugs (OR 4.1, 95% CI 1.3–12.9, p = 0.018)], fasting glucose(OR 2.7, 95% CI 1.5–4.8, p = 0.001), OGTT 2-hour glucose (OR 4.3, 95% CI 2.4–7.7, p < 0.001), during pregnancy; current anthropometry [waist circumference (OR 1.1, 95% CI 1.0–1.1, p = 0.007), hip circumference (OR 0.9, 95% CI 0.8–1.0, p = 0.001), BMI (OR 1.1, 95% CI 1.0–1.3, p = 0.001)]) were associated with T2DM. The prevalence of CVD risk factors was: insulin resistance 75% (95%CI 65.9-82.3), dyslipidaemia 74.6% (95%CI 68.3- 79.9), dysglycaemia 62.3% (95%CI 55.6-68.5), and raised blood pressure 41.4% (95%CI 35.0-48.0) and metabolic syndrome 60.9% (95%CI 54.3- 67.2). Of the 443 neonates exposed to HFDP during pregnancy, almost one-third [29.6% (95%CI 25.5 – 34.0)] were large-for-gestational-age (LGA) at birth and just over a fifth [21% (95%CI 15.4 – 27.8)] were either overweight or obese at preschool age. A strong association was found between maternal fasting glucose at HFDP diagnosis and birth weight zscore (OR 1.11, 95%CI 1 -1.22, p=0.046), maternal postprandial 2-hour glucose during the third trimester and weight z-score at birth (OR 1.23, 95%CI: 1.07 - 1.42, p = 0.005) and at preschool age (OR 1.37, 95%CI: 1.03 - 1.81, p = 0.031). Conclusion The high prevalence of T2DM and CVD risk factors in relatively young women and overweight and obesity in their offspring within 6 years of the index pregnancy demonstrates the need for context-specific interventions to prevent HFDP, to optimise screening for HFDP and to reduce cardiometabolic disease risk in the postpartum period.